(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Stryuk M. I. Trends in mobility of students and young scientists in the European educational and scientific area. The article highlights the new directions of the mobility of students, postgraduates and professors in the European educational and scientific are, the use of which in Ukraine will increase the competitiveness of the national education system. Particular attention is devoted to ways of solving the problem of brain drain.